Ethnocultural training as a factor in preventing ethnic alienation of a personality - A. A. Stepanova; E. E. Symaniuk (Образование и наука)
Introduction. In the modern world, the expansion of cross-cultural and international contacts, which are not necessarily positive and constructive, is a natural consequence of activisation of territorial and labour mobility of the population. The difficulty of adaptation of migrants to new living conditions belongs to the main causes of tension in interethnic relationship between indigenous peoples and migrants. The process of acculturation of migrants is accompanied by their desire to isolate themselves, which is perceived as a threat by the indigenous population of the country. Relevant scientific problem is the adaptation of migrants to unfamiliar socio-cultural environment without threatening the values of their own ethnic group.The aim of this research was to present the results of approbation of ethnocultural training for the prevention of ethnic alienation and the formation of biethnic identity.Methodology and research methods. The present research was based on the concept of “alienation-identity”. In the course of the ascertaining stage of diagnosis of migrants (n = 410), a set of methods of cross-cultural and ethnic psychology was used. The obtained results were processed through mathematical and statistical analysis using the Pearson correlation coefficient. A specially designed training for examinees with high rates on the scale of “alienation” (n=15) was developed and conducted. The results of the control stage of diagnosis were processed through mathematical and statistical procedures using the Wilcoxon signed-rank test.Results and scientific novelty. The main characteristics of ethnic alienation are defined: social disadaptation, depression and disharmony of a personality, nostalgia for native culture, individualism, identification with native ethnos. It is revealed that ethnocultural training contributes to the successful adaptation of migrants: personal development, instruction on the accepted standard of behaviour in a multicultural society and acquisition of intercultural communicative competence allow migrants to adapt to a new environment and to feel more confident and comfortable.Practical significance. The proposed methodological tool can be employed by experts, who implement the state programme on the migrants’ adaptation. Moreover, the methodological toolkit can be useful for representatives of social services, workers of information and adaptation centres and staff of other organisations working on migration issues.